Event Contextualization in Hadith Interpretation: A Framework for Reassessing Problematic Hadith Narratives - Abdul Sattar; Mohammad Fahmi bin Abdul Hamid; Khairul Azhar bin Meerangani; Moh. Nor Ichwan (UIN Sunan Kalijaga Yogyakarta, 2026)
Certain prophetic traditions (Hadīth) are still read through a textual-absolutist lens that treats situational speech as timeless law, often generating interpretations that feel ethically troubling or socially unworkable today. This article proposes event contextualization as a practical framework for reinterpreting “problematic” Hadīth by reconstructing the triggering event and its immediate social setting (asbāb al-wurūd), mapping variant transmissions, and then reassessing the report’s normative force in light of Qur’anic moral horizons and maqāṣid al-sharīʿah. Using qualitative textual analysis and contextual hermeneutics—supported by matn and sanad checks—the study examines recurring clusters of narrations frequently invoked in contemporary debates, especially on gender, minority relations, apostasy, and political obedience. The analysis suggests that many interpretive dead-ends arise when context-bound directives are universalized without attending to the occasion, audience, and intent of the Prophet’s instruction. By operationalizing event reconstruction alongside purposive ethical reasoning, the article offers a replicable way to distinguish time-sensitive instructions from transferable moral principles. It argues that this approach strengthens contemporary fiqh al-ḥadīth by reducing interpretive overreach while preserving the Prophetic moral aim.